EFFECTIVENESS OF EXPLAINER VIDEO-BASED ANEMIA PREVENTION EDUCATION ON PREGNANT WOMEN’S KNOWLEDGE AND ATTITUDES - Amelia, Tiara Pia; Sukesi, Sukesi; Sulistyowati, Dwi Wahyu Wulan; Isfentiani, Dina (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Anemia in pregnant women is a global health issue, often caused by a lack of knowledge and awareness regarding its prevention. Health education is one approach to improving the knowledge and attitudes of pregnant women toward anemia prevention. This study aims to evaluate the effectiveness of health education using explainer videos on the knowledge and attitudes of pregnant women. The research used a quasi-experimental method with a population of 76 primigravida pregnant women and a sample of 44 respondents selected through Simple Random Sampling. The independent variable was health education using explainer videos, while the dependent variables were the knowledge and attitudes of pregnant women. Data were analyzed using the Wilcoxon Signed Rank Test and Mann Whitney U Test. The resultsshowed a significant improvement in the knowledge and attitudes of pregnant women in the intervention group after watching the explainer videos, with a p-value of 0.000. The Mann-Whitney U Test indicated that explainer videos were more effective than leaflets. In conclusion, anemia prevention education using explainer videos effectively improves the knowledge and attitudes of pregnant women. Future studies should include an additional variable, such as the nutritional status of pregnant women.